Anterolateral ligament reconstruction associated with hamstring ACL reconstruction reduces the rate of repeat graft ruptures in a population of young athletes at follow-up in 2 years. (26th February 2021) - Laboudie, Pierre; Douiri, Adil; Graveleau, Nicolas; Bouguennec, Nicolas; Biset, Alexandre
Objectives: The rate of repeat graft ruptures in young athletes is a major concern after ACL reconstruction. Our objective was to evaluate the association between two reconstruction techniques and repeat ruptures, repeat surgery, return to sports and complications in center playing sportspersons younger than 20 years of age. Methods: A prospective study was conducted in patients under 20 years of age who were center players and who had primary ACL reconstruction with a semitendinosus graft (ST4) by a suspension technique, or a semitendinosus graft with suspension technique combined with independent anterolateral ligament reconstruction (ST4+ALL). Patients were followed up in a minimum of 2 years. Survival data from the Kaplan-Meier analysis were used as well as multivariate logistic regression to identify risk factors for repeat rupture. 203 patients (mean age, 16.3±2 years) with a mean follow-up of 40.6±11 months (24-63 months) were included. There were 101 patients in the ST4 group, and 102 patients in the ST4+ALL group. Results: There was a 9.9% repeat in ruptures in the ST4 group versus 5.8% in the ST4+ALL group (p=0.288). The rate of repeat ruptures in the ST4+ALL group was 5 times lower than in the ST4 group in multivariate analysis (odds ratio [OR], 0.201; 95% CI, 0.044-0.922). There was a 6.9% rate of secondary meniscal procedures in the ST4 group versus 1.9% in the ST4+ALL group (p=0.101). Differential laxity was 1.3±1.3 (-2 - 5) in the ST4 group versus 0.9±1.3 (-6 - 4.8) in the ST4+ALL group (p=0.008). There was a 42.2% return to the same sports level in the ST4 group versus 52% in the ST4+ALL group (p=0.178). The mean postoperative scores at the last follow-up were: IKDC: 83.3±14.3 and 82±14.4; ACL-RSI: 69.8±23.5 and 67.4±22.4; Tegner: 6.6±1.8 and 6.9±1.8 and Lysholm: 86.4±15.2 and 86±16.8; for ST4 and ST4+ALL groups, respectively. Conclusion: Anterolateral ligament reconstruction reduces the rate of repeat ruptures in athletes younger than 20 years of age after a semitendinosus graft. It is also associated with fewer secondary meniscal procedures, better control of laxity and a better rate of return to the same level of sports without further complications.